Association of COX-inhibitors with cancer patients’ survival under chemotherapy and radiotherapy regimens: a real-world data retrospective cohort analysis - Flausino, Lucas E.; Ferreira, Isabella N.; Tuan, Wen-Jan; Estevez-Diz, Maria Del Pilar; Chammas, Roger (Frontiers in Oncology, 2024)
IntroductionWe conducted an extensive, sex-oriented real-world data analysis to explore the impact and safety of non-steroidal anti-inflammatory drugs (NSAIDs) and selective COX-2 inhibitors (coxibs) on cancer treatment outcomes. This is particularly relevant given the role of the COX-2/PGE2 pathway in tumor cell resistance to chemotherapy and radiotherapy.MethodsThe study applied a retrospective cohort design utilizing the TriNetX research database consisting of patients receiving cancer treatment in 2008-2022. The treated cohorts included patients who were prescribed with coxibs, aspirin or ibuprofen, while individuals in the control cohort did not receive these medicines during their cancer treatment. A 1:1 propensity score matching technique was used to balance the baseline characteristics in the treated and control cohorts. Then, Cox proportional hazards regression and logistic regression were applied to assess the mortality and morbidity risks among patient cohorts in a 5-year follow-up period.ResultsUse of coxibs (HR, 0.825; 95% CI 0.792-0.859 in females and HR, 0.884; 95% CI 0.848-0.921 in males) and ibuprofen (HR, 0.924; 95% CI 0.903-0.945 in females and HR, 0.940; 95% CI 0.917-0.963 in males) were associated with improved survival. Female cancer patients receiving aspirin presented increased mortality (HR, 1.078; 95% CI 1.060-1.097), while male cancer patients also had improved survival when receiving aspirin (HR, 0.966; 95% CI 0.951-0.980). Cancer subtype specific analysis suggests coxibs and ibuprofen correlated with survival, though ibuprofen and aspirin increased emergency department visits’ risk. Secondary analyses, despite limited by small cohort sizes, suggest that COX inhibition post-cancer diagnosis may benefit patients with specific cancer subtypes.DiscussionSelective COX-2 inhibition significantly reduced mortality and emergency department visit rates. Further clinical trials are needed to determine the optimal conditions for indication of coxibs as anti-inflammatory adjuvants in cancer treatment.